Hemichorea caused by nonketotic hyperosmolar state: A case report and review of the literature. (2nd January 2017) - Raza, Hafiz Khuram; Jing, Jia; Cui, Guiyun; Liang, Xiaoqian; Hua, Fang; Zhang, Zunsheng; Tang, Hai; Shi, Hongjuan; Chen, Hao
Abstract: Our report involves a case of hemichorea caused by the nonketotic hyperosmolar state. We have analyzed the clinical data and relevant features of a patient who presented herself to the Affiliated Hospital of Xuzhou Medical University. The patient had unilateral involuntary movements for 1 month. We discovered that her blood glucose levels were very high. The patient underwent computed tomography (CT), magnetic resonance imaging (MRI), and magnetic resonance angiography (MRA), indicating right basal ganglia lesion. Control of the patient's blood glucose plus supportive treatment resulted in a significant improvement of her clinical state.